The institutional economics of rural development: Beyond market failure - Vladislav Valentinov; Sabine Baum (Journal of Central European Agriculture, 2008)
This paper examines and compares institutional arrangements addressing market failures endemic to rural areas. It argues that rural market failures cannot be satisfactorily addressed by for-profit firms and thus require the operation of third sector organizations, such as NGOs, cooperatives, and associations. The important role of these organizations in rural development is explained by the particular severity of rural market failures that inhibit the development of rural markets and thus constrain the operation of rural for-profit firms. This argument is applied to the development of rural tourism in Central and Eastern Europe. The rural tourist markets in this region are shown to fail in a number of ways that require recourse to tourism associations and other relevant third sector organizations. The paper concludes with calling for further research on developing the institutional economic theory of the rural third sector.
Keywords: 330; rural development; market failure; third sector; rural tourism; Central and Eastern Europe